2021
DOI: 10.48550/arxiv.2101.12631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Survey and Experimental Comparison of Graph-Based Approximate Nearest Neighbor Search

Abstract: Approximate nearest neighbor search (ANNS) constitutes an important operation in a multitude of applications, including recommendation systems, information retrieval, and pattern recognition. In the past decade, graph-based ANNS algorithms have been the leading paradigm in this domain, with dozens of graph-based ANNS algorithms proposed. Such algorithms aim to provide effective, efficient solutions for retrieving the nearest neighbors for a given query. Nevertheless, these efforts focus on developing and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The exact k-nearest neighbor problem asks for exact (true) k-nearest neighbors of every query point q. Another probabilistic version of the k-nearest neighbor search [44] , [61] The approximate version [2], [54], [1], [86] for every query point q ∈ Q, looks for its approximate neighbor r ∈ R satisfying d (q, r ) ≤ (1 + )d (q, NN(q)), where > 0 is fixed and NN(q) is the exact first nearest neighbor of q.…”
Section: The K-nearest Neighbor Search and Overview Of Resultsmentioning
confidence: 99%
“…The exact k-nearest neighbor problem asks for exact (true) k-nearest neighbors of every query point q. Another probabilistic version of the k-nearest neighbor search [44] , [61] The approximate version [2], [54], [1], [86] for every query point q ∈ Q, looks for its approximate neighbor r ∈ R satisfying d (q, r ) ≤ (1 + )d (q, NN(q)), where > 0 is fixed and NN(q) is the exact first nearest neighbor of q.…”
Section: The K-nearest Neighbor Search and Overview Of Resultsmentioning
confidence: 99%
“…Graphs can be used as effective indexes to accelerate nearest neighbors search [55,15]. Existing graph construction methods generally propose different rules to generate graphs, which cannot provide adaptivity for different workloads [102]. Baranchuk et al [5] employ DRL to optimize the graph for nearest neighbors search.…”
Section: Index Structure Constructionmentioning
confidence: 99%
“…At the other end of the spectrum of ANNS indices are graph-based indexing algorithms [28,33,34,43,51,52]. Several comparative studies [7,25,41,58] of ANNS algorithms have concluded that they significantly out-perform other techniques in terms of search throughput on a range of realworld static datasets. These algorithms are also widely used in the industry at scale.…”
Section: Shortcoming Of Existing Algorithmsmentioning
confidence: 99%
“…Even though this abstraction of ANN search is widely studied, it does not capture many important real-world scenarios where user interactions with a system creates and destroys data, and results in updates to 𝑃 (especially in the literature on graph-based ANNS indices [58]). For example, consider an enterprise-search scenario where the system indexes sentences in documents generated by users across an enterprise.…”
Section: Introductionmentioning
confidence: 99%